2015
DOI: 10.17921/2447-8733.2015v16n2p100-108
|View full text |Cite
|
Sign up to set email alerts
|

Autorregulação da Aprendizagem de Alunos de Cursos a Distância em Função do Sexo

Abstract: <p>O presente estudo está embasado na Psicologia Cognitiva/Teoria do Processamento da Informação e teve como objetivo analisar comparativamente a autorregulação da aprendizagem de alunos de cursos ofertados a distância em função do sexo. Um total de 305 alunos responderam a um questionário contendo 12 questões sobre o perfil dos estudantes e a uma Escala de Aprendizagem Autorregulada Online, com 24 itens distribuídos em seis Fatores: Estabelecimento de Metas, Estruturação do Ambiente, Estratégias para as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
2
2
1
4
Order By: Relevance
“…Moreover, students also reported having problems in time management and difficulty to monitor their comprehension while learning. Overall, the findings are consistent with the literature, which indicates that students enter university with gaps in many areas and lack strong and desirable strategic and self-regulatory skills to cope with the demands of higher education (Bembenutty, 2011;Boruchovitch and Ganda, 2013;Marini and Boruchovitch, 2014;ACT, 2016;Araújo et al, 2016;Pavesi and Alliprandini, 2016;Weinstein and Acee, 2018;Biwer et al, 2020). The attitude scale, on the other hand, had the highest mean and median in the LASSI.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, students also reported having problems in time management and difficulty to monitor their comprehension while learning. Overall, the findings are consistent with the literature, which indicates that students enter university with gaps in many areas and lack strong and desirable strategic and self-regulatory skills to cope with the demands of higher education (Bembenutty, 2011;Boruchovitch and Ganda, 2013;Marini and Boruchovitch, 2014;ACT, 2016;Araújo et al, 2016;Pavesi and Alliprandini, 2016;Weinstein and Acee, 2018;Biwer et al, 2020). The attitude scale, on the other hand, had the highest mean and median in the LASSI.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, research suggests that university students need to become more proactive, strategic, and self-regulated lifelong learners so they can meet the demands of global economy and modern workforce in rapid evolution (see Pew Research Center, 2016; Weinstein and Acee, 2018). Nevertheless, as the need for greater knowledge, skills, and adaptability in the workforce has increased, the number of students admitted to higher education without appropriate skills to learn has also increased (Bembenutty, 2011;Marini and Boruchovitch, 2014;ACT, 2016;Pavesi and Alliprandini, 2016;Endo et al, 2017;Medeiros and Bittencourt, 2017;Biwer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Results show that students generally report using learning and study strategies, with some strategies being reported more than others. These findings converge with research on strategic and self-regulated learning (Arcoverde et al, 2020 ; Iqbal et al, 2010 ; Pavesi & Alliprandini, 2016 ). The attitude scale showed the highest score.…”
Section: Discussionsupporting
confidence: 87%
“…Although Brazilian studies are still incipient, their findings converge with findings of international studies because both lines of research indicate that university students tend to use learning and study strategies (Boruchovitch et al, 2020;Iqbal et al, 2010;Pavesi & Alliprandini, 2016). They also show some differences in selfreported strategy usage by gender (Bartalo & Guimarães, 2008;Bender & Garner, 2010;Boruchovitch et al, 2020;Braten & Olaussen, 1998;Carpenter et al, 2014;Endo et al, 2017;Lins, 2013;Silva et al, 2016), course semester (Bortoletto, 2011;Boruchovitch et al, 2020;Endo et al, 2017;Marušić et al, 2017;Silva et al, 2016), age (Bortoletto, 2011;Boruchovitch et al, 2020;Braten & Olaussen, 1998;Martins, 2016), and program degree areas (Bartalo & Guimarães, 2008;Martins, 2016).…”
Section: Learning Strategies Self-efficacy and Sociodemographic Factorsmentioning
confidence: 78%
“…Ao abordar a característica pessoal, estudos evidenciam a existência de diferenças significativas entre fatores que influenciam o nível de utilização das estratégias metacognitivas de aprendizagem autorregulada, como idade, gênero, estágio no curso, tempo de estudo e desempenho acadêmico (ROSÁRIO, 2001;BEMBENUTTY, 2007; LOMBAERTS; ENGELS; VAN BRAAK, 2009;SCHLEIFER;DULL, 2009;PARRA et al, 2014;LIMA FILHO;LIMA;BRUNI, 2015;PAVESI;ALLIPRANDINI, 2015;SILVA et al, 2016;SILVA;BIAVATTI, 2018;SILVA et al, 2020).…”
Section: Introductionunclassified